Changes in the physicochemical components, polyphenol profile, and flavor of persimmon wine during spontaneous and inoculated fermentation. Issue 6 (14th April 2020) - Lu, Yao; Liu, Yaqiong; Lv, Jiawei; Ma, Yanli; Guan, Xiaolei
Abstract: Changes in the oenological parameters, total phenols, total flavonoids, and individual phenols of persimmon during spontaneous and inoculated fermentation were investigated. The volatile compounds and sensory character of the persimmon wine were compared and evaluated simultaneously. Results show that at the end of fermentation, spontaneous persimmon wine (SPW) has higher contents of total flavonoids, total phenols yet lower concentrations of alcohol and volatile compounds than inoculated persimmon wine (IPW). Catechin, salicylic acid, quercetin, and vanillic acid were the main phenolic compounds in both types of persimmon wine. There are six volatile components in the IPW with an OAV greater than 1, which are isoamyl acetate, ethyl hexanoate, methyl octanoate, ethyl octanoate, phenethyl acetate, and 2, 4‐di‐tert‐butylphenol, and these compounds contribute to the IPW with brandy and fruity sensory properties, while only three volatile components in SPW have OAV greater than 1, which are isoamyl acetate, ethyl hexanoate, and ethyl octanoate. Spontaneous fermentation increased the proportion of esters and alcohols in the overall volatile compounds. During sensory evaluation, IPW was characterized by "brandy, " "bitterness, " and low "sweetness, " and SPW has a high score of "sweetness, " "balance, " desirable "color, " and "body." Abstract : Changes in the oenological parameters, total phenols, total flavonoids, and individual phenolic compounds of persimmon wine during spontaneous and inoculated fermentation were investigated. The volatile compounds and sensory character of the persimmon wines were compared and evaluated simultaneously.